1973
DOI: 10.1177/0306624x7301700301
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Murderers

Abstract: ADOLESCENCE is a violent period of emotional development.Intra-psychic upheavals must be contained through the mustering of all available defence mechanisms, lest the ego in its search for identity destroys itself or disastrously acts out. Statistics show the commonest causes of death in the twelve to 20 age group to be auto or gun accidents, suicide and homicide. Criminal behavior and the onset of schizophrenia are not uncommon in adolescence.Some of the findings of our recent study of 100 &dquo;assaultive&dq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Only a few studies have examined sexual homicides perpetrated by juvenile offenders and most of these studies are based on case reports (5,(17)(18)(19)(20)(21)(22)(23). In fact, a review of the literature shows that most of the empirical work on juvenile SHOs has been published by Myers and colleagues (3,10,(12)(13)(14)(15)(16).…”
Section: Characteristics Of Sexual Homicide Perpetrated By Juvenile Omentioning
confidence: 99%
“…Only a few studies have examined sexual homicides perpetrated by juvenile offenders and most of these studies are based on case reports (5,(17)(18)(19)(20)(21)(22)(23). In fact, a review of the literature shows that most of the empirical work on juvenile SHOs has been published by Myers and colleagues (3,10,(12)(13)(14)(15)(16).…”
Section: Characteristics Of Sexual Homicide Perpetrated By Juvenile Omentioning
confidence: 99%
“…Only a few studies have examined sexual homicides perpetrated by juvenile offenders and most of these studies are based on case reports (5,17–23). In fact, a review of the literature shows that most of the empirical work on juvenile SHOs has been published by Myers and colleagues (3,10,12–16).…”
Section: Characteristics Of Sexual Homicide Perpetrated By Juvenile Omentioning
confidence: 99%
“…Within these, prevalence rates of psychotic disorders among matricidal offenders vary from 25%-100% among case studies, 33.3%-100% among descriptive studies, and 46.5%-100% among comparison studies. Of the 49 matricidal offenders reported across the 34 case studies of matricide, 34 (69.4%) were described with psychotic disorder diagnoses or symptomatology (though one case, "Luis," was reported in three separate publications; Russell, 1965Russell, , 1984Mack, Scherl, & Macht, 1973). In half of the comparison studies identified for this review, all (100%) of the matricidal offenders were diagnosed with schizophrenia or were psychotic at the time of the offense.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies mentioned or described matricidal offenders without matricide necessarily being the main focus of the publication (Tables 1-4). Russell, 1965Russell, , 1984 (4) Post-offense paranoid psychosis (1) Lifelong highly eroticized sadomasochistic relationship with mother. Shot mother to death.…”
Section: Methodsmentioning
confidence: 99%